The circles of life (1) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The circles of life (1)We are, as people, united by our diversity. We are, as persons, each unique. The way we feed ourselves, organise our own lives, touch other people s, the way we mourn and rejoice, are all different. We each do them all, but...